Persepsi, praktik, dan kebutuhan guru terhadap pendekatan deep learning dalam pembelajaran Bahasa Indonesia di sekolah menengah pertama - Maman Suryaman; Firstya Evi Dianastiti; Titis Kusumaningrum Witdaryadi Putri; Ruli Nur Safitri (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to (1) map the actual conditions of learning and (2) describe the needs of teachers for the development of Indonesian language learning models based on the deep learning approach. The research design uses descriptive qualitative with sample selection using proportional stratified random sampling techniques for schools in Yogyakarta City. Data collection techniques through observation, questionnaire documents, and interviews. Furthermore, data analysis with (1) data condensation, (2) data presentation, and (3) drawing conclusions. Based on the results of the study, the following conclusions were obtained: (1) current Indonesian language learning is still lacking in reading activities and faces challenges in the form of low student interest and involvement in reading activities. Teachers assess the need for efforts to increase motivation and reading comprehension through more interesting and contextual strategies. (2) Based on the needs analysis, learning tools need to be designed to: (a) improve critical and reflective thinking skills through meaningful reading activities, (b) optimize digital and multimodal media to strengthen motivation and reading comprehension, (c) Provide space for teachers as creative facilitators in adapting learning to student interests, and (d) foster reflective habits.